Joint resource allocation algorithm for clustering cognitive Internet of things - Xin LIU (物联网学报)
Cognitive Internet of things (CIoT) can improve spectrum utilization effectively through spectrum sensing and sharing,but spectrum sensing may generate overhead.Clustering CIoT was proposed to decrease sensing overhead,whose transmission rate could be improved through joint resource allocation.The network model and frame structure of the CIoT were proposed firstly,and the average transmission rate and interference power of the CIoT were deduced.Then,an optimization model was built to maximize the transmission rate through jointly optimizing the sensing time,sensing cluster head and transmission power,and a joint optimization algorithm was given to solve the optimization problem.Finally,the node clustering and cluster head selection algorithm of the CIoT was presented.The simulations show that the maximal transmission rate through joint resource allocation can be achieved and the transmission performance compared with the traditional schemes can be improved by the proposed scheme.